Letter - Hewson, A.
035-0134-001 Amalgamated Engineering Union General Office: 110, Peckham Road, London, S.E.15 BE UNITED & INDUSTRIOUS Branch Secretary's Address A. HEWSON, 14 WILLS CRESCENT, WHITTON PARK, HOUNSLOW MIDDLESEX. CHISWICK 2nd Bch Branch No. Your Reference Branch Seal CHISWICK 2 21 C.E. A.E.U. -9 SEP 1942 THE SECRETARY T.U.C. Dear Sir & Brother, The following resolution was carried unanimously at our last Branch meeting and a copy forwarded to our Executive Council :- "THIS BRANCH URGE THE T.U.C. TO APPROACH THE FOREIGN OFFICE WITH A VIEW TO OBTAINING THE RELEASE OF MEMBERS OF THE INTERNATIONAL BRIGADE, NOW IN CONCENTRATION CAMPS, BY CO-OPERATING WITH THE U.S.A. GOVERNMENT ON THIS QUESTION" Yours fraternally A. Hewson. EAB 292/946/35/134